Reducing Undergraduates Speaking Anxiety through Class Interactions and Oral Presentations - Aliyu, Muhammad Mukhtar; Korau, Shehu Muhammad; Basiru, Aminu (Asian Journal of Contemporary Education, 2019)
Proficiency in speaking English is an essential requirement for undergraduates particularly in English as a Second Language (ESL) learning context. However, many ESL undergraduates encounter challenges while learning speaking skills due to anxiety. Therefore, this study investigates the influence of class interactions and oral presentations on reducing undergraduates’ speaking anxiety. The study was conducted for a period of 12 weeks using a pre-post quasi-experimental research design. An intact class of 16 undergraduates in a stylistic class in north-eastern Nigeria was selected for the study. A questionnaire and semi-structured interviews were used to collect data for the study. Findings reveal that the students’ anxiety levels significantly reduced in all the five levels of speaking anxiety, psychological anxiety, fear of making grammatical mistakes, fear of negative evaluation, English classroom speaking anxiety, social-environmental factors, and perception factor. The findings also show that the students’ speaking anxiety is mostly due to fear of negative evaluation and social-environmental factor. The study makes some recommendations for teachers to help students to overcome speaking anxiety through classroom interactions and oral presentation.